Parto por cesárea y su asociación con el síndrome obstructivo bronquial agudo en pacientes de 12 a 36 meses de edad - Almanza-Mio, Carla (2023)
Objective. To determine the association between caesarean sections and the Acute bronchial obstructive syndrome (SOBA) in patients 12 to 36 months of age hospitalized at Vitarte-MINSA Hospital during 2017-2019. Material and methods. An analytical retrospective study of cases and controls was carried out. The population studied were 12 to 36-month-old patients hospitalized during 2017-2019, consisting of 306 children, 102 cases and 204 controls (1:2). The source of data collection was the medical history where the following variables are recorded: age, sex, caesarean section, APGAR, gestational age, breastfeeding, vaccination, overcrowding and siblings.  Results. The study population consisted mainly of 1-year-old children (53.27%) of female sex (52.29%). Caesarean section represents 41.18% of births and the association with the development of SOBA (OR = 2.50; 95% CI = 1.51-4.15; p <0.001) in comparison with vaginal delivery. Similarly, there is an association between breastfeeding (OR = 0.42; 95% CI = 0.23-0.78; p = 0.006), vaccination (OR = 0.56; 95% CI = 0.33-0, 94; p = 0.027) and overcrowding (OR = 1.77; 95% CI = 1.04-3.01; p = 0.034); however, there was no statistical difference between age (p = 0.343; 95% CI = 0.62-1.18%), sex (p = 0.871; 95% CI = 0.42-1.29), gestational age (p = 0.164; 95% CI = 0.71-1.06), APGAR (p = 0.685; 95% CI = 0.73-1.23) and siblings (p = 0.357; 95% CI = 0.89-1.39). Conclusion. Cesarean delivery is associated with the development of SOBA. Present a 2 times greater risk of suffering if born by caesarean section.